PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR SISWA PADA MATERI MENGIDENTIFIKASI UNSUR-UNSUR CERITA ANAK KELAS V SDN 22/12 SALEBBO KABUPATEN PANGKEP - Darlindah Lestari; Andi Adam; Ummu Khaltsum (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
Darlindah Lestari, 2025. The Effect of Using Audio Visual Media on Student Learning Outcomes in Identifying Elements of Children's Stories for Grade V of Sdn 22/12 Salebbo, Pangkep Regency. Thesis. Department of Elementary School Teacher Education. Faculty of Teacher Training and Education, Muhammadiyah University of Makassar, supervised by Andi Adam and Ummu Khaltsum. The main problem of this research is whether audio-visual media has an effect on students' learning outcomes in the material of identifying elements of children's stories in grade V of SDN 22/12 Salebbo, Pangkep Regency. This research aims to determine the effect of the use of audio-visual media on students' learning outcomes in the material of identifying elements of children's stories in grade V of SDN 22/12 Salebbo, Pangkep Regency. This research is a quantitative one. It uses a quasi-experimental design. In this experiment, there are two groups: the experimental group, given audiovisual treatment, and the control group, given no treatment. The subjects were 19 fifth-grade students at SDN 22/12 Salebbo, Pangkep Regency. The results of the study showed that based on the pretest of the experimental and control class learning outcomes, the average pretest value of the experimental group was 58.75 and the average pretest value in the control group was 43.18. After being given treatment to the control class and the experimental class, then given a posttest of the learning outcomes in the experimental class and the control class, the data obtained were the average value of the experimental class of 81.87 and the average value of the control class of 50.09. The average value of the experimental class was greater than the average value of the control class with a difference of 31.78. This proves that the use of audio-visual media has an effect on student learning outcomes in the material of identifying elements of children's stories in class V SDN 22/12 Salebbo, Pangkep Regency. Keywords: Quasi Experiment, Audio Visual Media and Listening Skills